Paese che vai, usanza che trovi. La concettualizzazione del paese in italiano - Paliczuk, Aleksandra (Neophilologica, 2016)
The elements and phenomena of physical space are a very fertile area for different ways of conceptualizing the world. As a result, they give rise to conceptual constructs which are then reflected by linguistic expressions in many languages. Our conceptualization of the world is mostly based on experience, especially physical one, that is to say, we conceive abstract concepts in terms of concrete ones. Among the theories dealing with cognitive linguistics, in the present paper the author makes a particular use of cognitive grammar, i.e. with a focus on the process of imagery in language, proposed by Ronald W. Langacker, and a relevant notion of linguistic image of the world elaborated by Polish researchers, Jerzy Bartmiński and Ryszard Tokarski. The paper is an attempt to present a cognitive analysis of the concept of paese (country) in Italian. It endeavors to explain how the Italians conceive and perceive the concept in question in opposition to its Polish and English equivalents.